The Role of Management Ability, Political Influence, and Financial Pressure on Fraudulent Financial Reporting: The Moderating Role of Credit Rating and a Comprehensive Mathematical Model of Corporate Governance in Banks Listed on the Tehran Stock Exchange - Fazaljoo, Parviz; Khalilpour, Mehdi; Ramezani, Javad; Rezaian, Ramazan; Babaei Khalili, Javad (Business, Marketing, and Finance Open, 2025)
One of the essential and significant factors influencing the quality of financial information and financial reporting is the political influence of management and business owners in the political environment and their relationships with political power circles. In this regard, the present study aims to examine the impact of management ability, political influence, and financial pressure on fraudulent financial reporting, considering the moderating role of credit rating and a comprehensive mathematical model of corporate governance in banks listed on the Tehran Stock Exchange. This study is applied in terms of its objective. The statistical population of this research includes all banks listed on the Tehran Stock Exchange during the period from 2015 to 2021. Considering the conditions and systematic elimination, 10 banks listed on the Tehran Stock Exchange were selected as the statistical sample. The testing and analysis of data were conducted using a multivariate regression model in the EViews software environment, and the generalized least squares (GLS) estimation method was employed. The results of data analysis indicate that credit rating and corporate governance influence the relationship between management ability, political influence, and financial pressure with fraudulent financial reporting in banks. The findings of this study can significantly assist policymakers, planners, and bank managers.